Orbiting Black/White Rays Produce an "Illusory" Gray Disk. (May 2016) - Anstis, Stuart; Dykmans, Neal; Kaneko, Sae; Cavanagh, Patrick
An orbiting ray pattern produces an unexpected gray disk. Here we demonstrate this visual effect and its possible insights into visual temporal integration.